The Role of Problem-Based Mufradat Learning on “ISMU fil Arabia” Activity - Muhammad Kusuma Wardhana; Mamluatul Hasanah; Syaiful Mustofa (Al-Muyassar: Journal of Arabic Education, 2026)
Nativism has been a pessimistic topic when discussing its implementation in the context of children's education. This happens because the flow of its universal ability, which has been carried since birth, is not influenced by external elements like an Arabic language environment gifted by teacher value. In fact, the understanding of Nativism is not that shallow; there are several indicators that are missed when looking at implicit phenomena in the role of Arabic language acquisition without involving this understanding. Using a phenomenological approach related to the "ISMU fil Arabia" activity, the researcher would explain the Nativism learning method in the Muhammadiyah Elementary environment, which has been proven to have produced students who are able to speak Arabic without external limitations from the school environment and teachers, Among them are the ability of students to find their own vocabulary based on the results of observations with their friends based on competitive learning themes; students are psychologically more emotionally mature and have quite high confidence because they are indoctrinated to carry the name of the school through this activity approach; the themes taught in this activity are structural and can be evaluated temporally through the implementation of Arabic-based competitions that have been determined by the school. There are indications that this finding is the starting point for increasing the trust of parents in the school. this phenomenon has become one of the sources of school promotion to get a higher accreditation value that can be achieved for free.